2019
DOI: 10.3847/1538-4357/ab0dfe
|View full text |Cite
|
Sign up to set email alerts
|

SN 2017czd: A Rapidly Evolving Supernova from a Weak Explosion of a Type IIb Supernova Progenitor

Abstract: We present optical and near-infrared observations of the rapidly evolving supernova (SN) 2017czd that shows hydrogen features. The optical light curves exhibit a short plateau phase (∼ 13 days in the R-band) followed by a rapid decline by 4.5 mag in ∼ 20 days after the plateau. The decline rate is larger than those of any standard SNe, and close to those of rapidly evolving transients. The peak absolute magnitude is −16.8 mag in the V-band, which is within the observed range for SNe IIP and rapidly evolving tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 106 publications
(117 reference statements)
0
14
0
Order By: Relevance
“…Thus, our linear fit (section 3.1) may not be valid at small 56 Ni masses, and it is possible that SESNe with a low 56 Ni mass ( 0.02M ) are observed as rapidly evolving transients with timescales shorter than 10 days 10 Actually, SN 2017czd in our sample is an SN IIb with very small 56 Ni mass of 0.003M . This object was classified as a rapidly evolving transient (Nakaoka et al 2019). Drout et al (2014) have estimated that the rate of rapidly evolving transients is 4-7 % of the core collapse SNe rate.…”
Section: Low 56 Ni Mass Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our linear fit (section 3.1) may not be valid at small 56 Ni masses, and it is possible that SESNe with a low 56 Ni mass ( 0.02M ) are observed as rapidly evolving transients with timescales shorter than 10 days 10 Actually, SN 2017czd in our sample is an SN IIb with very small 56 Ni mass of 0.003M . This object was classified as a rapidly evolving transient (Nakaoka et al 2019). Drout et al (2014) have estimated that the rate of rapidly evolving transients is 4-7 % of the core collapse SNe rate.…”
Section: Low 56 Ni Mass Objectsmentioning
confidence: 99%
“…Thus, SNe II can more easily be detected than SESNe, even if the 56 Ni mass is small. Indeed, several Ni-poor SESNe (M Ni 0.02M ) have been detected (Kasliwal et al 2010;Shivvers et al 2016;Nakaoka et al 2019). However, it should also be noted that none of these examples are just a low-luminosity version of canonical SESNe as they all show unusual properties.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys from the last two decades such as the Sloan Digital Sky Survey (SDSS, Frieman et al 2008), Palomar Transient Factory (PTF, Rau et al 2009), Zwicky Transient Factory (ZTF, Bellm 2014, Pan-STARRS (Scolnic et al 2018), and others (Guillochon et al 2017), have greatly increased the number of supernovae detected. In addition to detecting many more already well-understood classes of supernovae, previously unheard of transients were also detected, such as superluminous supernovae (Gal-Yam 2012; Bose et al 2018;Gal-Yam 2019), rapidly-decaying supernovae (Perets et al 2010;Kasliwal et al 2010;Prentice et al 2018;Nakaoka et al 2019;Tampo et al 2020), and transients with slow temporal evolution (Taddia et al 2016;Arcavi et al 2017;Dong et al 2020;Gutiérrez et al 2020). These discoveries have challenged existing theories of transients and suggest that a much broader range of events remain to be detected.…”
Section: Introductionmentioning
confidence: 99%
“…The initial masses were M1,i = 15M⊙ and M2,i = 1.5M⊙ and the initial period was Pi = 1000 days. Other examples include Benvenuto et al (2013) who fit a binary progenitor for the SN IIb 2011dh, and the recent paper by Nakaoka et al (2019) who fit a binary model to the SN IIb 2017czd. Podsiadlowski et al (1993) suggested that the progenitor of SN IIb 1993J was a binary system.…”
Section: Introductionmentioning
confidence: 99%